Pemberdayaan Masyarakat melalui Penanaman Mangrove untuk Mitigasi Bencana dan Pelestarian Ekosistem di Pesisir Pekalongan Utara - Mustofiatul Aini; Afifa Nur Hasanah; Dwi Ayu Septiyani; Grecia Adis Vanessa; M.Halim Barnanda; Mochammad Ariful Amar (Komunitas: Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2024)
The planting of mangroves in the northern district of Pekalongan is a mitigation effort. Where this area has a lot of coastal and coastal areas. This has caused the region to suffer disasters such as flooding and robbery. The function of the mangrove here as a barrier when the seawater is affected. With the presence of mangrove, the appearance of the sea waves can be suppressed so that the impact of damage on the land can be minimized. This effort is also supported by government regulations, namely the Disaster Management Act No. 24 of 2007. Mangrove planting in the northern district of Pekalongan City, especially in the Slamaran Beach area of Degayu Village, Northern Pekalongan, Central Java is a form of care for the environment and nature, which is carried out by the UKM-F Institution of Dycres UIN K.H. Abdurrahman Wahid Pekalongan, the Community of Joint Collaboration with the city of Pakalongan, as well as several other communities.Where it is also part of the community service activities carried out by students, students, and the community around. The purpose of this dedication is to reduce the risk of disasters or mitigation, especially floods and debris. It also builds a solid foundation for the sustainability of ecosystems and the well-being of local communities